Relational Communication in Digital Media: A Qualitative Study of Public Relations Practices in Indonesian Telecommunication - Ebthasarie, Kurnia Dwi; Prasetyo, Bambang Dwi; Kriyantono, Rachmat (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study examines the strategic orientation of Indosat’s Marketing Public Relations (MPR) in digital communication by addressing a key gap in current scholarship: despite the growing prominence of digital consumer engagement in Indonesia, limited research explicates how telecommunication brands operationalize soft-sell and hard-sell approaches within MPR frameworks and how these strategies shape relational dynamics with digital audiences. The research employs a qualitative descriptive design with purposive sampling of Indosat’s digital communication materials published between 2020 and 2024, focusing on three major campaigns: Emotional Connection, Indosat for Everyone, and Digitalization. Data were collected through systematic documentation of digital content across official social media platforms and complemented by non-participant observation, followed by thematic analysis to identify recurring narrative, visual, and relational patterns. The findings indicate that Indosat predominantly adopts a soft-sell MPR strategy manifested through emotionally driven storytelling, human-centered imagery, and value-based messaging that foregrounds inclusivity and social connection. Hard-sell elements appear more selectively and function primarily to deliver concise informational prompts related to product offerings. Analytical interpretation reveals that these soft-sell techniques strengthen brand–consumer relationships by fostering emotional resonance and perceived relational closeness, aligning with theories of emotional branding and digital engagement. The study contributes to digital communication and MPR scholarship by demonstrating how soft-sell relational strategies in Indonesia’s youth-driven digital ecosystem operate not merely as promotional tools but as mechanisms for constructing sustained brand loyalty and trust.